Financial Literacy, Financial Self-Efficacy, and Social Influence as Determinants of Investment Intention among Generation Z Students - Amalia Nur Chasanah; Hayu Wikan Kinasih; Suhita Whini Setyahuni (Jurnal Telekomunikasi dan Informatika, 2026)
This study aims to analyze the effect of financial literacy, financial self-efficacy, and social influence on investment intention among Generation Z students in Semarang. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 102 active university students in Semarang using purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that financial literacy does not have a significant effect on students’ investment intention. In contrast, financial self-efficacy and social influence have a positive and significant effect on investment intention. The R-square value of 0.547 indicates that the independent variables explain 54.7% of the variation in investment intention. These findings suggest that psychological and social factors play a more dominant role in influencing investment intention compared to financial knowledge. This study is expected to contribute to financial education development, particularly in enhancing investment intention among young generations.